2019
DOI: 10.1038/s41598-019-49802-w
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping protein-coding genes in human genome and their coincidental expression in tissues

Abstract: The completion of human genome sequences and the advancement of next-generation sequencing technologies have engendered a clear understanding of all human genes. Overlapping genes are usually observed in compact genomes, such as those of bacteria and viruses. Notably, overlapping protein-coding genes do exist in human genome sequences. Accordingly, we used the current Ensembl gene annotations to identify overlapping human protein-coding genes. We analysed 19,200 well-annotated protein-coding genes and determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Interestingly, in our study, we observed different clusters of overlapping cis-SAS genes ranging from 2 (paired overlapping genes) to 14 genes. Similar multigene-transcript overlapping regions have also recently been described in the human genome, where about 72 % of the overlapping protein-encoding genes showed a paired configuration, followed by more complex overlapping groups until reaching 22 overlapping genes in a protocadherin gene cluster on chromosome 5 [49]. Consequently, in terms of gene overlap, our data suggest that the physical chromosomal arrangement of the S. schenckii genes follows, to some extent, the pattern observed in other eukaryotic genomes where the different-strand overlapping type seems to be the most commonly adopted gene model [30].…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, in our study, we observed different clusters of overlapping cis-SAS genes ranging from 2 (paired overlapping genes) to 14 genes. Similar multigene-transcript overlapping regions have also recently been described in the human genome, where about 72 % of the overlapping protein-encoding genes showed a paired configuration, followed by more complex overlapping groups until reaching 22 overlapping genes in a protocadherin gene cluster on chromosome 5 [49]. Consequently, in terms of gene overlap, our data suggest that the physical chromosomal arrangement of the S. schenckii genes follows, to some extent, the pattern observed in other eukaryotic genomes where the different-strand overlapping type seems to be the most commonly adopted gene model [30].…”
Section: Discussionmentioning
confidence: 61%
“…Together, our findings indicate a role for both TOSPEAK and GDF6 in the joint, bone and cartilage malformations of the SYNS4 family [13]. Given that over 20% of human protein coding genes physically overlap [14] and that many others share promoters, and those like GDF6 that have regulatory elements nested within adjacent genes, the findings of this study have important implications for genotype-phenotype correlation studies and gene targeting strategies and for the design of gene therapies including those that use exogenous siRNA.…”
Section: Introductionmentioning
confidence: 59%
“…Today, we are seeing a renaissance of the field owing to the rapid advancement of genome-scale protein and RNA measurement tools and increasingly advanced prediction algorithms (Box 1 ), which have collectively revealed an abundance of overlapping genes and ORFs within cellular genomes. Recent work on the human genome has placed estimates of overlapping features much higher than previously thought 8 , 9 , encompassing 26% of all protein-coding genes 10 . This estimate will likely increase in the future as small ORFs (sORFs) encoding microproteins are increasingly being found in the human genome within previously annotated genes 11 13 .…”
Section: Introductionmentioning
confidence: 91%